Responses of Islamic Organisations to the ‎Enactment of Pancasila as Asas Tunggal for ‎Mass Organisations in Indonesia - Achmad Kemal Reza (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
This article was about the responses of some Islamic organistions to the decision of the New Order regime to enact Pancasila as sole basis for mass organization in Indonesia back in 1985. The highlighted organizations were PPP, HMI, PII, Muhammadiyah, and Nahdlatul Ulama. The article pointed out that this episode of state and Islam relationship in Indonesia showed the repressiveness of the new order regime and the responsiveness as well as adaptability of Islam towards of political sphere in Indonesia. Such responses ranged from stiff resistance in the case PII to open-handed acceptance in PPP. The article also illustrated how internal dynamic within Islamic organizations in which Islamic values and concepts were employed to justify or to rule out the admissibility of Pancasila as their sole basis for those organizations